Urgensi Hukum Responsif Di Masa Pandemi - Rumalutur, Muhammad; Ipaloat, Muhamad (IAIN Ambon, 2021)
This article wants to examine the phenomenon of public disobedience to various government policies in preventing the spread of covid-19. The author is of the view that this non-compliance should be answered by the government by using a responsive legal model in handling COVID-19. This article departs from the responsive legal theory proposed by Philipe Nonet and Philip Selznick. With responsive legal theory, we can see that public disobedience gives the message that the legal model used by the government in dealing with COVID-19 is largely autonomous and repressive law. This study uses a sociology of law approach with empirical legal research methods. In addition to searching documents both offline and online, we also use direct observation in data collection. This observation was carried out in Maluku.